Application of neodymium vanadate type nickel-based catalyst in hydrogen production by autothermal reforming of acetic acid

The preparation of zircon-type NdVO4-supported nickel-based catalysts by sol-gel method solves the problem of easy oxidation, sintering and carbon deposits in the acetic acid autothermal reforming reaction, achieving high activity and stability of the catalyst, and improving hydrogen yield and anti-carbon deposits.

CN119771433APending Publication Date: 2025-04-08CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510060838.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the existing acetic acid autothermal reforming reaction, the nickel-based catalyst is prone to oxidation, sintering and carbon accumulation, resulting in a decrease in catalyst activity or even inactivation.

Method used

The zircon-type NdVO4 oxide-supported nickel-based catalyst was prepared by sol-gel method to form a Ni-Nd-V-O active center, enhancing the catalyst's resistance to carbon deposits and sintering resistance.

Benefits of technology

The catalyst's resistance to carbon deposit and sintering ability in the acetic acid autothermal reforming reaction is improved, high activity and stability are maintained, the hydrogen yield is stable, and the by-product generation is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771433A_ABST
    Figure CN119771433A_ABST
Patent Text Reader

Abstract

The invention relates to a neodymium vanadate zircon type nickel-based catalyst for hydrogen production by autothermal reforming of acetic acid. The invention provides a novel catalyst which is stable in structure and high in activity aiming at the problem of inactivation of the existing catalyst in the autothermal reforming process of acetic acid. The molar composition of the catalyst is (NiO) a (NdO1.5) b (VO2.5) c, a ranges from 0.75 to 0.86, b ranges from 1.25 to 1.37, and c ranges from 1.21 to 1.42. A catalyst precursor is prepared by adopting a sol-gel method, a NiO phase and a zircon type NdVO4 phase are formed through roasting treatment, and the zircon type nickel-based catalyst Ni / NdVO4 with NdVO4 as a carrier is obtained. The catalyst provided by the invention effectively improves the stability of the catalyst and the yield of hydrogen, and effectively inhibits the generation of by-products such as methane, acetone and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an application of a neodymium vanadium zircon type nickel-based catalyst in hydrogen production by autothermal reforming of acetic acid, belonging to the field of hydrogen production by autothermal reforming of acetic acid. Background Art

[0002] At present, fossil energy accounts for about 80% of global energy consumption, which brings about problems such as greenhouse gas emissions and environmental pollution. With the continuous consumption of fossil fuels, hydrogen, as a clean, efficient and sustainable energy carrier, has good application prospects in power generation, aerospace and other fields. Biomass can be obtained through pyrolysis to obtain biomass oil with high energy density, and acetic acid (HAc), as the main component of biomass oil, can be used to produce cheap and renewable hydrogen resources through the acetic acid reforming process.

[0003] According to the change of reaction heat and different raw materials, the hydrogen production methods of acetic acid reforming can be divided into three categories: steam reforming (SR), partial oxidation reforming (POX) and autothermal reforming (ATR). As a traditional hydrogen production method, steam reforming can obtain a higher hydrogen yield, but the process is an endothermic reaction and requires external heat supply; partial oxidation reforming reaction is exothermic and can achieve self-heating, but the introduced oxygen can easily cause oxidation deactivation of the catalyst, and the hydrogen yield is low; autothermal reforming achieves thermal balance by adjusting the oxygen-carbon ratio in the feed gas. While maintaining a higher hydrogen yield, it significantly reduces the dependence on external heat sources and has significant advantages in hydrogen production.

[0004] In the process of autothermal reforming of acetic acid to produce hydrogen, the choice of catalyst is particularly important. Transition metal Ni-based catalysts are also highly active in cracking CC, CH and OH bonds, and have high selectivity for the product H2. However, in the autothermal reforming process, the carbon-containing intermediate CH x * (x = 0-3) further dehydrogenates to form C* species and wraps around the active metal Ni 0 At the same time, the local temperature at the front end of the catalyst bed in an oxidizing atmosphere can reach as high as 1000°C, which can easily cause the active species Ni 0 Sintering and oxidation lead to catalyst deactivation.

[0005] In order to solve various problems existing in the process of autothermal reforming of acetic acid with nickel-based catalysts, the present invention prepares a zircon-type NdVO4 oxide-loaded nickel-based catalyst by a sol-gel method, which is applied to the process of autothermal reforming of acetic acid to produce hydrogen and has the following characteristics.

[0006] The NdVO4 carrier constructed in the present invention is a tetragonal zircon structure, which is composed of [VO4] tetrahedron and Nd 3+The layers are stacked alternately along the [-1 1 1] direction, which is beneficial for the charge transfer to the surface. The electron cloud density is rearranged, which weakens the Ni 2+ With O 2- The chemical bonds between the Nd and NdO4 enhance the reduction ability of Ni. After reduction, the active component Ni is highly dispersed on the carrier, forming a large number of Ni-Nd-VO active centers, providing abundant active sites and promoting the adsorption and conversion of the reactant molecule CH3COOH. In the constructed NdVO4 zircon structure, the [VO4] tetrahedron is highly active to Nd 3+ The distortion of local coordination around the ions forms oxygen vacancies, in which some Ni 2+ Selective occupation of V by unequal charge substitution 5+ sites, causing the NdVO4 skeleton to deform, thus forming more oxygen vacancy defects; at the same time, the multivalent vanadium (V 3+ 、V 4+ 、V 5+ The redox properties between the species and the enhanced oxygen diffusion coefficient of the rare earth element Nd improve the lattice oxygen transfer ability of the NdVO4 carrier and the activation and migration ability of the active oxygen species O*. The higher oxygen mobility and abundant oxygen vacancy defects are conducive to the adsorption and activation of the reactants H2O and O2. The dissociated active oxygen species such as O* and OH* effectively inhibit the CH x * (x = 1-3) and other carbon-containing intermediates are dehydrogenated to form carbon deposits, and the gasification of the carbon deposit precursor C* is promoted, thereby improving the anti-carbon deposition performance of the catalyst.

[0007] At the same time, at the Ni-Nd-VO active center of the catalyst of the present invention, the alkalinity of the rare earth element Nd neutralizes the Lewis acid site of the V species, thereby improving the overall basicity of the catalyst. A large number of medium-strength Lewis basic sites are formed to target and adsorb CO2 molecules through electrostatic interactions, polarize their electron distribution to promote the breaking of C=O bonds, thereby promoting the gasification of carbon species and driving the Boudouard reaction in reverse (CO2+C→2CO), thereby improving the anti-carbon deposition performance of the catalyst. In the constructed NdVO4 carrier, the spatial structure of alternating layered stacking and the lattice defects formed by local distortion regulate the electron cloud distribution of the active component Ni and enhance the metal-carrier interaction. At the same time, the anchoring effect inside the carrier mesoporous structure anchors small-sized Ni grains on the catalyst surface, effectively inhibiting their aggregation and growth, and improving the catalyst's anti-sintering ability, thereby showing good catalytic activity in the hydrogen production process.

[0008] The innovation of the catalyst composition and structure of the present invention improves the catalyst's ability to resist carbon deposition and sintering in the acetic acid autothermal reforming reaction; the activity test results of the catalyst applied to the acetic acid autothermal reforming reaction also show the excellent activity and stability of the invented catalyst. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a new catalyst with stable structure, high conversion rate, good selectivity, resistance to sintering and oxidation resistance, in view of the problems that the active components of the catalyst in the existing acetic acid autothermal reforming reaction are easily oxidized, sintered and carbonized, resulting in reduced catalyst activity or even deactivation.

[0010] The present invention uses Ni as an active component and adopts a sol-gel method to prepare a NdVO4 zircon-type nickel-based catalyst to form a Ni-Nd-VO active center. The catalyst of the present invention is used in an acetic acid autothermal reforming hydrogen production reaction. When the reaction temperature is 650°C, the acetic acid conversion rate is close to 100%, and the hydrogen yield is stabilized at about 2.8 mol-H2 / mol-HAc.

[0011] Technical solution of the present invention:

[0012] The present invention adopts a sol-gel method to prepare a NdVO4 zircon-type nickel-based catalyst in view of the characteristics of acetic acid autothermal reforming. The molar composition of the catalyst of the present invention is (NiO) a (NdO 1.5 ) b (VO 2.5 ) c , wherein a is 0.75-0.86, b is 1.25-1.37, and c is 1.21-1.42; the composition according to the weight percentage of the oxides is: nickel oxide is 14.0%-16.0%, neodymium oxide is 52.5%-57.8%, vanadium pentoxide is 27.5%-32.2%, and the sum of the weight percentages of each component is 100%.

[0013] The specific preparation method and activity test steps are as follows:

[0014] 1) According to the molar composition of each component in the catalyst (NiO) a (NdO 1.5 ) b (VO 2.5 ) c , where a is 0.75-0.86, b is 1.25-1.37, and c is 1.21-1.42. Weigh a certain amount of nickel nitrate, neodymium nitrate, and ammonium metavanadate into a beaker, add deionized water, and stir to dissolve in a 70°C water bath to obtain solution #1;

[0015] 2) Prepare a mixed solution 2# of citric acid and ethylene glycol according to the molar ratio of the total number of metal cations: citric acid: ethylene glycol of 1:1:1;

[0016] 4) In a 70°C water bath, slowly add solution 2# to solution 1#, continue stirring until a gel is formed, and then place in an oven at 105°C and dry for 24 hours to obtain a catalyst precursor;

[0017] 5) The dried precursor sample was placed in a tube furnace, heated to 750°C at a heating rate of 10°C / min, and calcined at this temperature for 4 hours to obtain a nickel-based catalyst with NdVO4 as the carrier, forming NiO phase and zircon-type NdVO4 phase. Its typical crystal structure is shown in the attached figure. Figure 1 As shown, a mesoporous structure was constructed at the same time, and its typical BJH pore size distribution is shown in the attached Figure 2 As shown;

[0018] 6) After the catalyst is reduced in a H2 atmosphere at 600-800°C, it is purged with a nitrogen atmosphere and a mixed gas with a molar ratio of CH3COOH / H2O / O2 / N2=1 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5) is introduced through the catalyst bed to carry out an autothermal reforming reaction at a reaction temperature of 600-800°C.

[0019] Beneficial effects of the present invention:

[0020] 1) The catalyst of the present invention uses Ni as an active component, and a nickel-based catalyst with NdVO4 zircon structure as the main body is prepared by a sol-gel method. ① The constructed NdVO4 carrier is a tetragonal zircon structure, which is a tetragonal crystal system I41 / amd space group, and a chain network parallel to the c-axis is formed by alternating co-edges of [NdO8] polyhedrons and [VO4] tetrahedrons, wherein the [NdO8] unit is formed by two interlaced tetrahedrons, one of which is elongated along the c-axis and the other is compressed along the c-axis, and the bond length in each tetrahedron is the same, and the [VO4] tetrahedron has a strong affinity to Nd 3+ The distortion of local coordination around the ions forms oxygen defects; among them, some Ni 2+ Selective occupation of V by unequal charge substitution 5+ sites, causing the NdVO4 skeleton to deform, thereby forming more oxygen vacancy defects; ② At the same time, the multivalent vanadium (V 3+ 、V 4+ 、V 5+) species and the enhanced oxygen diffusion coefficient of rare earth element Nd improve the lattice oxygen transfer ability of NdVO4 carrier and the activation and migration ability of active oxygen species O*. The higher oxygen mobility and abundant oxygen vacancy defects are conducive to the adsorption and activation of acetic acid autothermal reforming reactants H2O and O2. The dissociated active oxygen species such as O* and OH* effectively inhibit CH x * (x = 1-3) and other carbon-containing intermediates are dehydrogenated to form carbon deposits, and the gasification of the carbon deposit precursor C* converted into acetic acid is promoted (C* + O* → CO and C* + CO* → CO2), thereby improving the anti-coking performance of the catalyst.

[0021] 2) In the NdVO4 zircon structure constructed by the catalyst of the present invention, [VO4] tetrahedron and Nd 3+ The alternating stacking of layers is conducive to the transfer of charge to the surface, which reduces the Ni 2+ With O 2- The chemical bonds between them enhance the reduction ability of Ni. After reduction, the active component Ni is highly dispersed on the carrier to form a large number of Ni-Nd-VO active centers, which provide abundant active sites and promote the adsorption and conversion of autothermal reforming reactant molecules CH3COOH, H2O, and O2. At the same time, on the Ni-Nd-VO active center, the alkalinity of the rare earth element Nd neutralizes the Lewis acid sites of the V species, improves the overall basicity of the catalyst, and a large number of medium-strength Lewis basic sites are formed to target and adsorb CO2 molecules through electrostatic interactions, polarize their electronic distribution to promote the breaking of C=O bonds, thereby promoting the gasification of carbon species C* and driving the Boudouard reaction in reverse (CO2+C→2CO), thereby improving the catalyst's anti-coking performance.

[0022] 3) The present invention introduces Nd and V components to construct a new NdVO4 zircon-type nickel-based catalyst with a mesoporous structure, thereby improving the specific surface area and pore structure of the catalyst; in the constructed NdVO4 carrier, the spatial structure of alternating layered stacking and the lattice defects formed by local distortion regulate the electron cloud distribution of the active component Ni and enhance the metal-carrier interaction; at the same time, the anchoring effect inside the carrier mesoporous structure anchors small-sized Ni grains on the catalyst surface, effectively inhibiting their aggregation and growth, and improving the catalyst's anti-sintering ability, thereby exhibiting good catalytic activity in the hydrogen production process.

[0023] 4) The results of the acetic acid autothermal reforming reaction show that the catalyst of the present invention can induce the efficient conversion of acetic acid, has a high hydrogen yield, and effectively inhibits the generation of by-products, and has the characteristics of anti-sintering and anti-carbon deposition. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1: X-ray diffraction spectrum of the catalyst of the present invention;

[0025] Figure 2 : BJH pore size distribution diagram of the catalyst of the present invention. DETAILED DESCRIPTION

[0026] Reference example one

[0027] 1.175g of Ni(NO3)2·6H2O and 12.497g of Al(NO3)3·9H2O were weighed, poured into a beaker, and an appropriate amount of deionized water was added, and the mixture was stirred thoroughly until dissolved to obtain solution 1#; 7.849g of citric acid and 2.318g of ethylene glycol were weighed, and an appropriate amount of deionized water was added to prepare a mixed solution 2# of citric acid and ethylene glycol; solution 2# was mixed with solution 1#, and then the water bath temperature was kept at 70°C and stirring was continued until a gel was formed; the obtained gel was placed in an oven at 105°C and dried for 24h to obtain a catalyst precursor, and the precursor sample was placed in a tubular furnace, heated to 750°C at a heating rate of 5°C / min, and calcined at this temperature for 4 hours to obtain a CDUT-NA catalyst, forming a nickel-based catalyst supported on Al2O3; the weight percentage composition of the catalyst in terms of oxides is: nickel oxide (NiO) is 15.1%, aluminum oxide (AlO 1.5 ) is 84.9%.

[0028] The activity evaluation of acetic acid autothermal reforming reaction was carried out in a continuous flow fixed bed reactor. The catalyst was ground and tableted, then sieved into 20-40 mesh particles, 0.1-0.2 g was weighed and loaded into the reactor, and reduced in H2 at a temperature of 600-800°C for 1 hour; then the mixed solution of acetic acid and water was injected into the vaporizer by a constant flow pump for vaporization, mixed with oxygen, and nitrogen was used as the internal standard gas to form a reaction raw gas with a molar composition of CH3COOH / H2O / O2 / N2=1 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5), and this raw gas was introduced into the catalytic reaction bed. The reaction conditions were 600-800°C, normal pressure, and space velocity of 20000-60000 mL / (g-catalyst∙h), and the reaction tail gas was analyzed online by gas chromatograph.

[0029] The activity of the catalyst CDUT-NA was investigated by the autothermal reforming reaction of acetic acid. After hydrogen reduction at 700℃, the initial conversion rate of the catalyst for acetic acid was 99.6% under the reaction conditions of atmospheric pressure, space velocity 25000mL / (g-catalyst∙h), reaction temperature 650℃, and raw gas molar composition CH3COOH / H2O / O2=1 / 4.0 / 0.28. After 10 hours of reforming reaction, the acetic acid conversion rate dropped to 64.6%, the H2 yield gradually decreased to 0.65mol-H2 / mol-HAc, the CO2 selectivity fluctuated around 49.0%, the CO selectivity fluctuated around 38.5%, the byproduct methane selectivity fluctuated around 5.6%, and the byproduct acetone selectivity increased to around 35.7%. The characterization results show that the catalyst has low activity and more byproducts in the autothermal reforming process of acetic acid, sintering and carbon deposition occurred during the reaction, and the overall stability is poor.

[0030] Embodiment 1

[0031] 1.168g of Ni(NO3)2·6H2O, 2.875g of Nd(NO3)3∙6H2O and 0.767g of NH4VO3 were weighed and poured into a beaker, and a certain amount of deionized water was added to dissolve to obtain solution 1#; 3.601g of citric acid and 1.064g of ethylene glycol were weighed, and an appropriate amount of deionized water was added to prepare a mixed solution 2# of citric acid and ethylene glycol; solution 2# was mixed with solution 1#, and then the water bath temperature was kept at 70°C and stirred until a gel was formed; the obtained gel was placed in an oven at 105°C and dried for 24h to obtain a catalyst precursor, and the precursor sample was placed in a tubular furnace and heated to 750°C at a rate of 10°C / min, and calcined at this temperature for 4 hours to form a NiO phase and a tetragonal zircon-type NdVO4 phase, and a nickel-based catalyst Ni / NdVO4 with NdVO4 as a carrier, namely, a CDUT-NNV catalyst, was obtained, and its typical crystal structure is shown in the attached Figure 1 The catalyst was tested by nitrogen low temperature physical adsorption, and the typical mesoporous structure is shown in the attached Figure 2 As shown; the catalyst molar composition is (NiO) 0.80 (NdO 1.5 ) 1.32 (VO 2.5 ) 1.32 The catalyst has a weight percentage composition of 15.0% nickel oxide, 55.2% neodymium oxide, and 29.8% vanadium pentoxide in terms of oxides.

[0032] The activity of the catalyst CDUT-NNV was investigated by the autothermal reforming reaction of acetic acid. After hydrogen reduction at 700°C, the catalyst had a stable 100% conversion rate for acetic acid, a stable H2 yield of about 2.8 mol-H2 / mol-HAc, a stable CO2 selectivity of about 68.8%, and a CO selectivity of about 30.8% under the reaction conditions of atmospheric pressure, space velocity of 25000 mL / (g-catalyst·h), reaction temperature of 650°C, and raw gas molar composition of CH3COOH / H2O / O2=1 / 4.0 / 0.28. No byproducts of methane and acetone were detected, and the catalyst activity remained stable without deactivation. The CDUT-NNV catalyst was characterized by low-temperature nitrogen physical adsorption, as shown in the attached Figure 2 As shown, the specific surface area is 9.9m 2 / g, pore volume is 0.08cm 3 / g, concentrated pore size distribution, average pore size of 11.4nm, most probable pore size of 2.9nm, belonging to mesoporous material. Characterization results show that the catalyst exhibits high and stable activity during the reaction, no sintering occurs, no obvious carbon deposition occurs, and the production of by-product acetone is effectively suppressed.

Claims

1. Application of neodymium vanadium zircon type nickel-based catalyst in the process of hydrogen production by autothermal reforming of acetic acid, characterized in that: The catalyst was reduced in a H2 atmosphere at 600-800°C for 1h, nitrogen was used as the internal standard gas, and a mixed gas with a molar ratio of CH3COOH / H2O / O2 / N2=1.0 / (1.3-5.0) / (0.21-0.35) / (2.5-4.5) was introduced through the catalyst bed to react at a reaction temperature of 600°C-800°C; the catalyst was prepared by the following method: according to the catalyst composition, a certain amount of nickel nitrate, neodymium nitrate, and ammonium metavanadate were weighed in a beaker, deionized water was added, and solution 1# was obtained by fully stirring and dissolving in a 70°C water bath; according to the total number of moles of metal cations: The molar ratio of citric acid to ethylene glycol is 1:1:1, and a mixed solution 2# of citric acid and ethylene glycol is prepared; in a 70°C water bath, the 2# solution is slowly added dropwise to the 1# solution, and stirring is continued until a gel is formed, and then the mixture is placed in an oven at 105°C and dried for 24 hours to obtain a catalyst precursor; the obtained precursor sample is placed in a tubular furnace, heated to 750°C at a heating rate of 10°C / min, and calcined at this temperature for 4 hours to form a NiO phase and a zircon-type NdVO4 phase, and a nickel-based catalyst Ni / NdVO4 with NdVO4 as a carrier is obtained; the molar composition of the catalyst in terms of oxide is (NiO) a (NdO 1.5 ) b (VO 2.5 ) c , wherein a is 0.75-0.86, b is 1.25-1.37, and c is 1.21-1.42; the composition according to the weight percentage of the oxides is: nickel oxide is 14.0%-16.0%, neodymium oxide is 52.5%-57.8%, vanadium pentoxide is 27.5%-32.2%, and the sum of the weight percentages of each component is 100%.

2. The use of the neodymium vanadium zircon type nickel-based catalyst according to claim 1 in the process of producing hydrogen through autothermal reforming of acetic acid, characterized in that: The catalyst is composed of 15.0% nickel oxide, 55.2% neodymium oxide and 29.8% vanadium pentoxide in terms of oxide weight percentage.